Grosse Akta dalam Menghadapi Kredit Macet - Phireri, Phireri; Amir, Amir; Suardi, Suardi (Jurnal Litigasi Amsir, 2022)
Grosse is different from other notary deeds, as well as is a tool of evidence for the parties as well as the actual and developing legal institutions that follow the flow speed in the development of the business, industry, and credit. this is because today’s credit problems can not be separated from Grosse deed because the bond loan agreement is generally in the form of Grosse pour indeed, as stated in Article 224 HIR/258 R.B.g by using Grosse deed in case of obstacles in the debt settlement the debtor to the creditor no longer require regular claims process that will take a very long time but with the use of Grosse deed then simply by requesting the establishment of the local Chief District Court. of benefits and advantages, especially in the face of bad loans. The problem is not as simple as Grosse’s deed in theory, because in practice there are still many problems that hinder the course of execution of the many requests. Where gross deed executions are addressed to the Court, there are some applications that are acceptable and some are not acceptable for the execution carried out. this is due to the presence of factors that may cause obstacles to the execution of the deed in court Grosse.